The Journeymen Tailors' Union of America. A study in trade union policy ([University of Illinois, 1918)
With bibliogr., index and tabs. Repr.: University of Illinois studies in the social sciences. Vol. VII, 1918, no 4 december, p. 431-571. Facsimile reprint: New York, N.Y. etc., Johnson Reprint Cooperation, 1970.